2016
DOI: 10.1017/s1041610216001666
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury (TBI) in older adults: aging with a TBI versus incident TBI in the aged

Abstract: Approximately 39 million older adults (age >65) were evaluated for traumatic brain injury (TBI) in United States emergency departments during the 2-year period from 2009 to 2010, representing a 61% increase in estimates from prior years (Albrecht et al., 2015a). Across the lifespan, an estimated 5.3 million Americans are living with a TBI-related disability (Centers for Disease Control and Prevention (CDC), 2003). With improved recognition and management, more individuals experiencing TBI are surviving to die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
(33 reference statements)
0
21
0
Order By: Relevance
“…The prevalence in World Trade Center responders is 12.8% or 33,000 persons who are at risk for dementia as they age. CDC has estimated that across the lifespan 5.3 million older Americans are living with TBI …”
Section: Alzheimer's Disease Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence in World Trade Center responders is 12.8% or 33,000 persons who are at risk for dementia as they age. CDC has estimated that across the lifespan 5.3 million older Americans are living with TBI …”
Section: Alzheimer's Disease Overviewmentioning
confidence: 99%
“…However, it has also showed that this causality is not linear, being rather more complex and involving multiple causes . Recent advances on the understanding of Alzheimer's disease genetics and molecular pathways have helped identifying novel cerebrospinal fluid and blood biomarkers, as well as the development of promising new therapies that are currently being tested . Among the promising therapies, are those which target Aβ production, direct targeting of Aβ and tau, and immunotherapy .…”
Section: Research and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most likely, her injury during childhood began a degenerative process sufficient to culminate in cognitive decline and MCI in later adulthood. Our examination will be of particular interest to those assessing the clinical importance of patients who are “aging after having suffered TBI” in contradistinction to those who experience “incidents of TBI during aging” (Peters, ).…”
Section: Discussionmentioning
confidence: 99%